Perceived discrimination and depressive symptoms among US Latinos: the modifying role of educational attainment. Issue 3 (3rd April 2019) - Ward, Julia B.; Feinstein, Lydia; Vines, Anissa I.; Robinson, Whitney R.; Haan, Mary N.; Aiello, Allison E.
ABSTRACT: Objective: Despite growing evidence that discrimination may contribute to poor mental health, few studies have assessed this association among US Latinos. Furthermore, the interaction between discrimination and educational attainment in shaping Latino mental health is virtually unexplored. This study aims to examine the association between perceived discrimination and depressive symptoms and the modifying role of education among a population of Mexican-origin adults. Design: We utilized population-based data from 629 Mexican-origin adults (mean age = 52.8 years) participating the Niños Lifestyle and Diabetes Study (2013–2014). Perceived discrimination was defined as responding 'sometimes' or 'often' to at least one item on the 9-item Everyday Discrimination Scale. High depressive symptoms were defined as scoring ≥10 on the CESD-10. We used log-binomial and linear-binomial models to estimate prevalence ratios (PR) and prevalence differences (PD), respectively, of high depressive symptoms for levels of perceived discrimination. Final models were adjusted for age, sex, education, cultural orientation, and nativity. General estimating equations were employed to account for within-family clustering. Results: Prevalence of perceived discrimination and high depressive symptoms were 49.5% and 29.2%, respectively. Participants experiencing discrimination had higher depressive symptom prevalence than those never or rarely experiencing discrimination [PR = 1.94, 95% confidence interval (CI): 1.46–2.58; PD = 0.19, 95% CI: 0.12–0.27]. The strength of this association varied by education level. The association between discrimination and depressive symptoms was stronger among those with >12 years of education (PR = 2.69; PD = 0.24) compared to those with ≤12 years of education (PR = 1.36; PD = 0.09). Conclusion: US Latinos suffer a high burden of depressive symptoms, and discrimination may be an important driver of this burden. Our results suggest that effortful coping strategies, such as achieving high education despite high perceived discrimination, may magnify discrimination's adverse effect on Latino mental health.